A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Dexamethasone treatment alters insulin, leptin, and adiponectin levels in male mice as observed in DIO but does not lead to alterations of metabolic phenotypes in the offspring - Clemens Bönisch; Martin Irmler; Laura Brachthäuser; Frauke Neff; Mareike T. Bamberger; Susan Marschall; Martin Hrabě de Angelis; Johannes Beckers (Mammalian Genome, 2016)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)